Identification of Amino Acid Residues in Influenza A Virus PA-X That Contribute to Enhanced Shutoff Activity - Oishi, Kohei; Yamayoshi, Seiya; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2019)
The influenza virus protein PA-X modulates the host immune responses and viral pathogenicity through suppression of host protein expression. The endonuclease active site in the N-terminal region, the basic amino acid cluster in the C-terminal PA-X-specific region, and N-terminal acetylation of PA-X by NatB are important for the shutoff activity of PA-X. Here, we focused on the shutoff activity of PA-X derived from the A/California/04/2009 and A/WSN/33 viruses because these two PA-X proteins differ in their shutoff activity. Mutagenesis analysis revealed that proline and serine at positions 28 and 65, respectively, play a central role in this difference. Furthermore, we found that P28 and S65 also affect the shutoff activity of PA-X derived from other influenza virus subtypes. These data demonstrate that P28 and S65 contribute to enhanced shutoff activity of PA-X.